2023
DOI: 10.3389/fendo.2023.1110824
|View full text |Cite
|
Sign up to set email alerts
|

The bidirectional relationship between endometriosis and microbiome

Abstract: Endometriosis has been described by many different theories of pathogenesis over the years. It is now also appreciated to be a state of chronic inflammation, and the role of immune dysfunction in its development has been proven. There is increasing evidence to support the role of the microbiome in the formation and progression of endometriosis via inflammatory pathways. The dysbiosis seen in endometriosis is thought to be both causative and a consequence of the pathogenesis. Gut, peritoneal fluid and female re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…This predisposition is believed to be reflected clinically in infertility, changes in the junctional zone [ 36 ], and severe dysmenorrhoea from the first menstruation onwards [ 37 ], even before endometriosis lesions have formed. Another consequence of this predisposition is the high risk of initiating endometriosis lesions soon after puberty [ 38 ], when the oxidative stress of retrograde menstruation or infection or the microbiome [ 39 ] increases the risk of additional incidents.…”
Section: Results: the 10 “Cardinal Sins”mentioning
confidence: 99%
“…This predisposition is believed to be reflected clinically in infertility, changes in the junctional zone [ 36 ], and severe dysmenorrhoea from the first menstruation onwards [ 37 ], even before endometriosis lesions have formed. Another consequence of this predisposition is the high risk of initiating endometriosis lesions soon after puberty [ 38 ], when the oxidative stress of retrograde menstruation or infection or the microbiome [ 39 ] increases the risk of additional incidents.…”
Section: Results: the 10 “Cardinal Sins”mentioning
confidence: 99%
“…Wei et al (116) showed that Gram-negative bacteria can increase the number and volume of lesions and the number of macrophages in a mouse model of EMs by producing GUS. Other researchers have shown that there are significant differences in the gut microbiome in EMs patients compared to normal individuals, and the levels of expression of inflammatory factors, nuclear factors-κB p65, and cyclooxygenase-2 increased in EM patients (117). This suggests that an imbalance of the gut microbiome activates the inflammatory pathway of the gut-brain axis and participates in the progression of EMs.…”
Section: Gut Dysbiosis and Emsmentioning
confidence: 92%
“…To date, correction of the gut microbiota with antibiotics, probiotics, or fecal bacterial transplantation is a hopeful method for improving the clinical management of endometriosis. [49,50,51] Authors Contribution:…”
Section: Medical Treatmentmentioning
confidence: 99%